Transformational Leadership Practices of School Principals in Developing a Quality Culture in Remote Junior High Schools: A Mixed-Method Study - Putri, Alfiona Sultana; S, Rustan; Akbar, Akbar (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2025)
This study investigates the transformational leadership practices of a school principal in developing a quality culture in a remote junior high school in Indonesia. While transformational leadership has been extensively studied in urban and well-resourced contexts, limited attention has been given to how it is applied and adapted in geographically isolated and resource-constrained school environments. Using a mixed-method research design, this study combined qualitative data from interviews, observations, and document analysis with quantitative data obtained through teacher and student questionnaires. The findings revealed that the principal exhibited strong transformational leadership behaviors, including inspirational motivation, idealized influence, intellectual stimulation, and individualized consideration. These practices translated into the development of a collaborative, visionary, and quality-oriented school culture, despite infrastructural and logistical limitations. A localized leadership model was formulated, emphasizing four key elements: vision-driven motivation, ethical role modeling, innovation support, and personalized empowerment. The study contributes theoretically by extending the applicability of transformational leadership theory to rural and underserved educational settings. Practically, it offers a replicable leadership framework for school principals and policymakers aiming to foster school improvement under challenging conditions. Methodologically, the study affirms the value of mixed-method inquiry in capturing the complex dynamics of leadership in education. Overall, the research underscores the strategic role of principal leadership in cultivating sustainable quality culture in remote schools.